Analysis of the Results of Basic Life Support and First Aid Training for Soccer School Coaches in East Java - Arisanti, Shinta; Pribadi, Florence; Santoso, Rahajoe Imam; Lifindra, Bella Meylani; Kencanawati, Nathania Dwi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2022)
The Provincial Association of All-Indonesian Football Associations in East Java as the Association of Football Associations, has duties and responsibilities in managing, developing and advancing East Java football. One of the problems faced by the Provincial Association is the first treatment of sports injuries. New football coaches receive training on Basic Life Support and First Aid for injuries/traumas when participating in C-licenced trainer certification while becoming a coach at a football school does not require a C-licence qualification. The purpose of this study was to determine the skills and abilities of football coaches regarding Basic Life Support and First Aid for injuries to players when the medical team is not available so that permanent disability and athlete death can be avoided. The method used is a survey method by assessing the skills of Football School coaches in understanding Basic Life Support and First Aid. The results show that only 12 have heard/done 38.7% of First Aid training. Of the 31 coaches, 18 people understand what to do to check consciousness when a player faints are 58.1%. How to free the airway in players suspected of having neck injuries, only 13 coaches knew about 41.9%. Only 12 coaches knew how to free the airway in players without neck injuries by 38.7%. 15 trainers who know the maximum time for breathing examinations are 48.4%.